Fe3+/Fe2+ Mycobactin‐Complex Electrochemistry as an Approach to Determine Mycobactin Levels in Urine. Issue 3 (5th March 2015) - McBride, Nicholas S.; Hall, Elizabeth A. H.
Abstract Mycobacterium acquire iron by producing siderophores called mycobactins, with an extremely high affinity complexation of Fe3+. The iron complex shows distinctive electrochemistry predicting 18 orders of magnitude greater affinity of the mycobactin for Fe3+ than Fe2+. A heterogeneous standard rate constant, ks of the order of 10−5 cm s−1 confirms quasi reversible electrochemistry and based on the equilibrium in the presence of excess solution Fe3+/Fe2+ the oxidation and reduction peaks for the siderophore complex could be calibrated for ferric mycobactin J (FeMJ). FeMJ spiked urine collected from cows showed a matrix effect on the current peak height. For example, 240±15 µM FeMJ was estimated in 600 µM spiked urine. However, in the presence of excess solution Fe(acac)3 the same sample yielded an estimated 580±25 µM FeMJ.